Development of Water-Resistant Autohesive Strength of Polyethylene Plates with Photografting of Alkyl (Meth)Acrylates - Kazunori Yamada; Yuki Kazama; Yuji Kimura (Macromol, 2023)
This study aims to confer autohesive strength to polyethylene (PE) plates by swelling the grafted layers, which were formed on the PE plates grafted with alkyl (meth)acrylate monomers, with 1,4-dioxane, and subsequently heat-pressing them. For the methyl methacrylate (MMA)-grafted PE (PE-g-PMMA) plates, the location of grafting was restricted to the outer surface region and the grafted layer with higher densities of grafted PMMA chains was composed. When the grafted PE plates were immersed in 1,4-dioxane, and then heat-pressed while applying the load, autohesion was developed. The substrate failure was observed for the PE-g-PMMA plates and the grafted amount at which the substrate failure was observed decreased with the procedures that decreased the methanol concentration of the solvent, the MMA concentration, the grafting temperature, and the heat-press temperature, and/or increased the load. The lowest grafted amount of 45 μmol/cm2 for the substrate failure was obtained under the conditions where the PE-g-PMMA plate prepared at 0.75 M and 60 °C in a 70 vol% aqueous methanol solution was heat-pressed at 60 °C while applying the load of 2.0 kg/cm2. The swelling of the grafted layers with 1,4-dioxane considerably contributed to the development of autohesion, bringing the inter-diffusion of grafted PMMA chains and coincident entanglement of grafted PMMA chains during the heat-pressing. The fact that the substrate failure occurred indicates that an autohesive strength higher than the ultimate strength of the used PE plate was obtained. Our approach provides a novel procedure to develop the water-resistant autohesion of PE plates.